1999
DOI: 10.1021/ja984440q
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Distyrylbenzene Chromophores:  Effect of Fluorine Regiochemistry on Molecular Properties and Solid-State Organization

Abstract: A series of fluorinated distyrylbenzene (DSB) derivatives were synthesized and studied in order to probe the effect of fluorine substitution on molecular properties and on the arrangement of molecules in the solid state. Reaction of 1,4-diiodobenzene with 4-fluorostyrene or pentafluorostyrene in the presence of Pd(OAc)2 gives trans-trans-bis(4-fluorostyryl)benzene (2F t ) and trans- trans-1,4-bis(pentafluorostyryl)benzene (10F t ), respectively. Bis(2,5-difluorostyryl)benzene (4F t ) was prepared by the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(107 citation statements)
references
References 71 publications
4
103
0
Order By: Relevance
“…This shift is triggered by the mesomeric (±M, with + and -indicating a donor and acceptor effect, respectively) and/or inductive (±I) effects associated with the substituents, leading to an asymmetric (de)-stabilization of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels. A striking exception is substitution with fluorine atoms, in which case the subtle balance between the M and -I effects leads to either a blue-or red-shift, depending on the number and position of the substituents [75] as well the nature of the molecular backbone. [75][76][77] A red-shift of the adiabatic transition energy upon substitution does not necessarily imply a red-shift of the vertical transition energy and of the absorption maximum (A max ), because the latter are also influenced by the shape of the torsional potential in the electronic ground state.…”
Section: Substitution Effectsmentioning
confidence: 99%
“…This shift is triggered by the mesomeric (±M, with + and -indicating a donor and acceptor effect, respectively) and/or inductive (±I) effects associated with the substituents, leading to an asymmetric (de)-stabilization of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels. A striking exception is substitution with fluorine atoms, in which case the subtle balance between the M and -I effects leads to either a blue-or red-shift, depending on the number and position of the substituents [75] as well the nature of the molecular backbone. [75][76][77] A red-shift of the adiabatic transition energy upon substitution does not necessarily imply a red-shift of the vertical transition energy and of the absorption maximum (A max ), because the latter are also influenced by the shape of the torsional potential in the electronic ground state.…”
Section: Substitution Effectsmentioning
confidence: 99%
“…Gladysz and co-workers reported a convenient and scalable procedure for the cross-couplings of fluorous alkenes (80) with aryl bromides (81) using a modified Jeffery version of the MizorokiHeck reaction (Scheme 16) [72]. Fluorous alkenes (80) reacted with aryl monobromides and polybromides (81), such as 1,3-and 1,4-C6H4Br2, 1,3,5-C6H3Br3, 1,3,5-C6H3Br2Cl, 1,4-XC6H4Br (X = CF3, C8F17, COCH3, CN, 1,4-OC6H4Br), 1,2-O2NC6H4Br, 5-bromo-isoquinoline, 5-bromopyrimidine, 3-bromo-5-methoxypyridine, and 3,5-dibromopyridine, under the modified Mizoroki-Heck coupling conditions to afford the corresponding fluorophilic adducts (82) in good to high yields. Typically, 1.2-2.4 equiv.…”
Section: Fluoroalkylated Alkenes As the Cross-coupling Partnersmentioning
confidence: 99%
“…A series of fluorinated distyrylbenzene (DSB) derivatives (124 and 126) were synthesized by Pdcatalyzed Mizoroki-Heck cross-couplings (Scheme 24) [81]. The reaction of 1,4-diiodobenzene (122a) with pentafluorostyrene (123) or 4-fluorostyrene (125b) in the presence of Pd(OAc)2 gave trans-trans-1,4-bis(pentafluorostyryl)benzene (124a) or trans-trans-bis(4-fluorostyryl)benzene (126a).…”
Section: Other Fluorine-containing Alkenes As the Cross-coupling Reagmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of¯uorine in molecular crystals and its in¯uence on crystal packing have been comparatively rarely studied [for examples, see Hayashi & Mori (1998) and Renak et al (1999)], given the wealth of information available on the effect of the F atom in biological chemistry (Filler et al, 1993). The interactions of organic¯uorine with other atoms within a crystal lattice are weak and, indeed, it has been observed that, when organically bonded,¯uorine hardly ever acts as a hydrogen-bond acceptor (Dunitz & Taylor, 1997).…”
Section: Commentmentioning
confidence: 99%